2005
DOI: 10.1002/jat.1082
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of albumin, triglycerides, total protein and glucose in rats are altered after oral treatment with low doses of 13-cis-retinoic acid or all-trans-retinoic acid

Abstract: Currently used to treat severe acne, 13-cis-retinoic acid (13-cis-RA) is under investigation for its anticancer effects as is the isomer, all-trans-retinoic acid (all-trans-RA). Here, the effects of oral 13-cis-RA or all-trans-RA treatment on serum chemistry, leptin and adiponectin levels were evaluated. Adult Sprague-Dawley rats were gavaged once daily for 7 consecutive days with 13-cis-RA (7.5 or 15 mg kg(-1)), all-trans-RA (10 or 15 mg kg(-1)) (n=24/sex/dose), or soy oil (n=16/sex) and blood was sampled 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
4
23
0
1
Order By: Relevance
“…Vitamin A supplementation in the diet of genetically obese WNIN/Ob rats resulted in a decreased total body weight related to a decrease in adiposity and lowered glycemia and insulinemia [65,66]. Interestingly, similar results were reported using either all- trans or 13- cis RA [67]. Sakamuri et al attributed this anti-obesity effect to the ability of vitamin A to decrease the activity of the 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), an enzyme involved in the synthesis of glucocorticoids [68], hormones that have been shown to promote pre-adipocyte differentiation [69].…”
Section: Vitamin Amentioning
confidence: 79%
“…Vitamin A supplementation in the diet of genetically obese WNIN/Ob rats resulted in a decreased total body weight related to a decrease in adiposity and lowered glycemia and insulinemia [65,66]. Interestingly, similar results were reported using either all- trans or 13- cis RA [67]. Sakamuri et al attributed this anti-obesity effect to the ability of vitamin A to decrease the activity of the 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), an enzyme involved in the synthesis of glucocorticoids [68], hormones that have been shown to promote pre-adipocyte differentiation [69].…”
Section: Vitamin Amentioning
confidence: 79%
“…Although it is an effective therapy for acne, isotretinoin is associated with significant adverse effects, including cheilitis, dry skin and mucous membranes [22], epistaxis, increased risk of cutaneous Staphylococcus aureus infections [23], myalgias, and pseudotumor cerebri [24]. Frequently reported blood chemistry abnormalities in isotretinoin users include elevated levels of triglycerides and cholesterol [25], elevated LDL concentrations and decreased HDL concentrations [26]. In our current study, isotretinoin treatment often caused significant elevations in cholesterol, LDL-C, and triglycerides, which are comparable with results seen in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Only scarce results on the effect of metabolites of vitamin A and notably retinoic acid were reported [63,64]. Zhang et al observed a decrease of adiponectin mRNA levels in white adipose tissue of mice treated with a single dose of all-trans retinoic acid [65], whereas comparable treatment had no effect on adiponectin plasma concentration in rats [66]. The downregulatory effect of all-trans retinoic acid on adiponectin expression was also confirmed in 3T3-L1 adipocytes [25,67].…”
Section: Vitamin a And Pro-vitamin A Carotenoids As Direct And Indirementioning
confidence: 99%